More than Somebody’s Pleasure: The Analysis of Reading for Pleasure in Education using Cognitive Psychology Perspective - Faiz Fatihul 'Alwan; Ayu Ulivia; Tina Hayati Dahlan (MultiTech Publisher, 2023)
Reading for pleasure is a reading activity that provides the reader with flexibility in terms of the type of reading materials and the time to read it. There are various advantages offered from reading for pleasure compared to other reading activities, not only having a good impact on children, it also provides enormous benefits to adults. This study aims to reveal the cognitive processes that occur during reading for pleasure activities based on empirical findings. The discussion in this study will also involve a comparison of cognitive processes with other types of reading activities. A qualitative approach was used in this study for both the data collection and analysis. The results of this study indicate that reading for pleasure is a reading activity which has many benefits. Analysis from the perspective of cognitive psychology shows that positive impacts such as the ability to focus the attention, adaptation to distraction, and the ability to relate the content with prior knowledge can be obtained through this reading activity. Regarding its implications in the context of education, reading for pleasure can be a solution to foster reading habits and affect students' cognitive abilities in a positive way. .